Musealisation and ethno-cultural stereotypes in Persian art: the case of Baluch carpets ca. 1870s – 1930s - Kassiani Kagouridi (Journal of Art Historiography, 2023)
This study examines Baluch carpets’ musealisation and the prejudiced view that carpets woven by Persians are superior to the carpets of tribal groups– a view expressed in 1876 by Robert Murdoch Smith in the exhibition catalogue of the Persian collection he had purchased for the South Kensington Museum. To do so, travel memoirs, museum registers and exhibition catalogues in European and US museums ca. 1870s-19030s are revisited. The scope is to refine Baluch weavings as museum objects and delineate how tribal carpets were integrated in museums within ethno-cultural stereotypes in Persian art and the re-discussion between ‘fine’ and ‘applied’ arts.